Von Menschen und Tieren im Frühwerk Monika Marons - Paola Quaderelli (Recherches Germaniques)
Animals often turn up in Monika Maron’s novels; they remind Maron’s restless characters of their own animal nature and put them in touch with their most genuine essence, providing thus a liberating feeling of happiness. This article examines the relationship between animals and men in Maron’s novels from the 80’s, wherein animal freedom offers a striking contrast with the repressive reality of the GDR. The hybrid creatures that the reader of these early novels encounters embody the desire of Maron’s female characters to overcome the opposition between human and animal. On the other side, characters who play a role in the repressive political system of the country are represented as people who fear animals and are anxious to maintain the distance between human and animal. This presents an interesting analogy to the reflections of those contemporary philosophers, like Giorgio Agamben, who pointed out the political dimension of the separation between human and animal and who argued at the same time in favor of bridging that gap.